Pengaruh Sistem Informasi Akuntansi dan Sistem Pengendalian Internal Terhadap Kinerja Pemerintahan (Studi Kasus pada Instansi Pemerintah Kota Batu) - Likuwatan, Mayatisari; Malikah, Anik; Mawardi, M. Cholid (Universitas Islam Malang, 2023)
The purpose of this study was to find out how the influence of the Accounting Information System and Internal Control System on Government Performance